International cooperation in the field of vocational education and training : concepts, approaches, and empirical findings from a German perspective - Frommberger, Dietmar [Verfasser]; Pilz, Matthias [Verfasser]; Gessler, Michael [Verfasser] (My University, 2021)
From a German perspective, international cooperation in the field of vocational education and training is often aimed at the development of dual structures of vocational education and training systems in partner countries. In part 1 of this contribution, conceptual approaches and empirical findings on the transferability and replication of the dual system abroad are presented. In part 2, we focus on international cooperation in vocational education and training, and in part 3, we discuss prerequisites and possibilities for the development of German 'core principles’ of a dual system in partner countries. This contribution concludes with an overall reflection." (Author's abstract ; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; 370; Berufsbildung; Internationale Zusammenarbeit; Duales System; Bildungstransfer; Partnerländer